Pembuatan Pupuk Organik Cair dari Bahan Cangkang Telur Bersama Masyarakat Pembudidaya Sayuran di desa Naga Beralih - Bachry, Syamsul; Saputra, Andi; Ayu, Febri; Sari, Vebrita; Yusri, M. (Journal of Social and Community Service, 2023)
Household waste is an environmental problem that has the potential to be very dangerous if alternative solutions are not found to reduce it. One of the household wastes that is often found is egg shells. This waste is often found in cake sellers, restaurants, households and laying hen farms. This waste is often found in cake sellers, restaurants, households and laying hen farms. Generally, Indonesian egg shells have not been managed properly so people only throw them away or store them in empty areas in village areas. The aim of community service is 1) a solution for managing egg shells as organic fertilizer, 2) Providing training regarding the use of egg shell waste as organic fertilizer. The method used is direct outreach and training with the vegetable cultivating community. The materials used are cassava leaves, animal waste, fruit waste, EM4 and palm sugar. The results of community service activities for vegetable cultivators show good results. The organic fertilizer solution that has been mixed with various other supporting materials is then put into a bottle and tightly closed, then fermented for up to 10 days at a temperature of 40°C. After 10 days, liquid organic fertilizer is put into packaging bottles. The organic fertilizer produced can be used directly by the cultivating community.